Evaluation of the effect of different methods of curacy on women with adenomyosis in the first half of pregnancy on the development of early gestative complications - Nosenko, O. M.; Kosyuga, O. M. (Journal of Education, Health and Sport, 2019)
Pregnancy in women with adenomyosis has an increased risk of multiple obstetric complications, especially early pregnancy losses. The purpose of the study was to conduct a comparative analysis of the impact of different methods of curation of pregnant women on the development of early gestational complications. Material and methods. There were 89 pregnant women with a pre-radiologically diagnosed adenomyosis. The main group (n = 45) included women receiving 10 mg twice daily hydrochloride per os from the time of pregnancy to 20 weeks of gestation; folic acid per os at 400 mcg once a day from the moment of establishment of pregnancy to 12 weeks of pregnancy; solution of L-arginine aspartate per os 5 ml four times daily from 8th to 10th and from 14th to 16th week of pregnancy. The comparison group (n = 44) was comprised of women receiving folic acid 400 μg once daily from the time of pregnancy until 12 weeks of gestation. In the instrumental examination of women, ultrasound was performed with Doppler. To evaluate the function of the yellow body of pregnancy, chorion and placenta it were determined such hormones of peripheral blood as placental lactogen, human β-chorionic gonadotropin, progesterone, free estriol and PAPP-A. Serum concentrations of total nitrite anions (NO2-) and free L-arginine were studied in serum. Early pregnancy complications were assessed. Results. Carrying out medical support for early gestation in pregnant women with adenomyosis according to the developed scheme has led to a decrease in the number of presence of pain syndrome in 12 weeks of gestation by 2.67 times (OR 0.17; 95% CI 0.06-0.47; p<0,01); at 18 weeks - at 3.78 (OR 0.14; 95% CI 0.04-0.42; p<0.01); decrease in placenta volume by 1.39 times (p<0.01) and 1.53 (p<0.01); IP in spiral arteries 1.08 times (p<0.01) and 1.07 (p<0.04), and in uterine arteries respectively 1.19 times (p>0.04) and 1,51 (p<0.01); increase in serum progesterone levels 1.07 times (p <0.01) and 1.13 (p<0.01); placental lactogen - by 1.12 (p<0.01) and in 1.63 (p<0.01); β-HCG at 1.17 (p<0.01) and 1.50 (p<0.01); free estriol - by 1.14 (p<0.01) and 1.16 (p<0.01); PAPP-A - 1.14 (p<0.01) and 1.19 (p<0.04), free L-arginine - 1.07 times (p<0.03) and 1.18 (p<0.01); nitrite anions (NO2-) - by 1.07 (p<0.01) and 1.19 (p<0.01). The use of the proposed method of pregnancy management in women with adenomyosis led to a statistically significant reduction in complications in the first half of pregnancy: the risk of termination of pregnancy by 2.56 times (OR 0.22; 95% CI 0.09-0.55), the number of cases of retrochorial hematoma - 2.13 (OR 0.36; 95% CI 0.13-0.99), early miscarriages - 3.07 (OR 0.26; 95% CI 0.08-0.88), late miscarriages - by 2.05 (OR 0.47; 95% CI 0.08-2.68), total miscarriages - 2.73 (OR 0.27; 95% CI 0.09-0.77). Conclusions. Patients with adenomyosis are at high risk for early gestational complications, such as the risk of termination of pregnancy, retrochorial hematomas and miscarriages. Preventive treatment support for such pregnant women should include, along with folic acid preparations, dydrogesterone preparations from the time of pregnancy up to 20 weeks, a solution of L-arginine aspartate per os for 2 weeks during periods of deep placentation.